ANALISIS AKTIVA PAJAK TANGGUHAN DAN DISCRETIONARY ACCRUAL SEBAGAI PREDIKTOR MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Ni Putu Eka Widiastuti; Elsa Chusniah (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
Abstract This research is to test the deferred tax assets in predicting earnings management in companies in Indonesia. Further research will compare the deferred tax assets compared to the accrual model that has been used as a measure of earnings management to avoid losses. The population in this study is manufacturing companies listed in Indonesia Stock Exchange during 2007 through 2009. The sample in this study are 20 companies that selected using purposive sampling method. Data is tested using logistic regression method. Result of this research shows that the deferred tax assets and discretionary accrual significant effect on earnings management. Keywords: Earnings Management, Accrual, Deferred Tax Assets.